Retrospective survey on drugs seized in Niger from 2013 to 2016 and state of the art on drug analysis and detection techniques - Salifou Karimoune, Fadjimata; Adamou Rabani; Zangui Hamissou (Technium Social Sciences Journal, 2021)
Drug is a substance, which trouble brain. One of the reasons for juvenile delinquency is drug use. The present work is a retrospective study based on seizures of drugs made by the Niger courts and. Evaluation of the drug utilization by people according to the statistics of drug seizures from 2013 to 2016 of the Central Office for the Suppression of Illegal Traffic in Narcotics (OCRTIS). According to the statistics of drug seizures from 2013 to 2016 of the Central Office for the Suppression of Illegal Traffic in Narcotics (OCRTIS). Nine (9) types of drugs belonging to six (6) families were seized in Niger including: Amphetamines, Cannabis, Crack, Cocaine, Diazepam, Ephedrine, Heroin, Methamphetamines and Tramadol. These come from all countries bordering Niger but also from East Africa and Central Africa and the data gathered was analyzed using MS Excel. It should be noted that the percentage of those charged varies according to age group whose: the under 18’s are 6%, 59% are between 18 and 29 years, 25% are between 30 and 39 years, the 40 years and over are 10%. So most of the people which have been arrested are minors between 18 and 39 years old. In addition, it is necessary to mention 2% of women against 98 % of men in the said sale and consumption. If the number of seizures increases each year, the possibility of drug consumption by its users would also grow and highlights important diseases related to their consumption. Thus, the more appropriate implication of the blood and urine tests of these drug users.